Anti-inflammatory effects of Eucheuma denticulatum and Padina minor crude extracts in an egg albumin-induced paw edema of ICR mice - ALITA S. LABIAGA; MICHAEL B. PLES; MARCO NEMESIO E. MONTAŇO (Nusantara Bioscience, 2024)
Abstract. Labiaga AS, Ples MB, Monta?o MNE. 2024. Anti-inflammatory effects of Eucheuma denticulatum and Padina minor crude extracts in an egg albumin-induced paw edema of ICR mice. Nusantara Bioscience 16: 245-250. Inflammation indicates that the body is unhealthy and exposed to harmful stimuli. Hence, it is important to study natural compounds with anti-inflammatory activities. This study assessed the anti-inflammatory effects of the aqueous and ethanolic crude extracts of Eucheuma denticulatum (N.L. Burman) F.S. Collins & Hervey and Padina minor (Yamada, 1925) in an egg albumin-induced paw edema of male Institute for Cancer Research (ICR) mice. This in vivo study investigated the anti-inflammatory activity of the aqueous and ethanolic crude extracts from E. denticulatum and P. minor at a dose of 100 mg/kg and compared it with a commercial anti-inflammatory drug (mefenamic). The study showed a significant decrease in the paw size, body temperature, neutrophil count, and white blood cell count in mice treated with seaweed crude extracts. The results of the first hour showed that the Eucheuma ethanolic extract treatment had the highest decrease in paw size, and the highest temperature reduction was found in the treatment of Padina ethanolic extract. There are significant differences in paw size, temperature, and leukocytes between the control and treatment groups, as well as between the aqueous and ethanolic extracts. The extracts from E. denticulatum significantly decrease the temperature, paw size, and leukocytes, which are the inflammation markers of egg albumin-induced paw edema. The diverse seaweed in the country has various pharmacological potential that should be studied further to maximize utilization.